Pengembangan Sistem Informasi Penjualan dan Pemesanan Plywood berbasis Web menggunakan Teknologi Framework Laravel dengan memanfaatkan Payment Gateway Midtrans (Studi Kasus: CV Mirai Alam Sejahtera) - Shabrina Amalia Putri; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CV Mirai Alam Sejahtera is a private company whose main business is the marketing and manufacture of Plywood, LVL (Laminated Veneer Lumber), and Veneer base in Indonesia. Until now, the customer service processes such as ordering, payment, and report recap are done manually. This causes problems such as, errors in recording order data, difficulty in accessing information by customers, and inefficient transaction checking processes. From the description of the problem, to facilitate the ordering and payment process, a website for the sales and ordering information system was developed which aims to make it easier for the company. This plywood sales and ordering information system will be integrated with the proposed payment gateway using Midtrans and developed using the SDLC (System Development Life Cycle) waterfall model. The languages ​​used in programming are PHP, Laravel framework, and MySQL database. The tests carried out are testing tests using the blackbox testing method with a 100% valid success rate. Meanwhile, the usability test using the Nielsen Attributtes of Usability (NAU) method got 84% results which were considered a very feasible system. In the efficiency value, the result is 4.25 out of 5.00, which means the system has succeeded in providing satisfaction to users in placing orders and payments on the plywood sales and ordering information system.